Altitudinal distribution of the functional feeding groups of aquatic macroinvertebrates using an ecological network in Andean streams - Serna, Juan Pablo; Fernandez, David; Velez, Fabio; Ruiz, Julián; Breckling, Broder; Aguirre, Néstor (Revista de Biología Tropical, 2022)
Introduction: Analysis of functional feeding groups (FFG) in aquatic macroinvertebrates is important in understanding the structure, function, and dynamics of ecological processes ecosystems. Modularity refers to the degree of compartmentalization of food webs and varies between -1 and 1. A network with a modularity value close to 1 is resilient to disturbances and can be interpreted as an indicating factor for the stability of communities. Objective: In this study, we analyzed the trophic structure of benthic macroinvertebrates in La Nitrera stream, the San Juan River, and the Cauca River. Methods: The study was supported by ecological networking techniques using Gephi software. We studied nine sites in dry, rainy, and transition seasons in 2017 and 2018, monitoring changes in the altitude gradient. At each of the sites, the organisms were captured and determined, and physicochemical and hydraulic information was obtained. Results: The variance component analysis allowed to explain the variability of the data by relating the following environmental variables: FFG, diversity, richness, modularity, season, and time. Simple multifactorial ANOVA indicated that significant changes in FFG were associated with altitude, and modularity to time. The allocation of the FFG was done by stomach analysis and secondary information. Conclusion: The transition season had the highest modularity, possibly due to the recolonization of some biotopes caused by the decrease in riverbed velocity. La Nitrera and San Juan presented higher values than the Cauca, which may indicate that the altitudinal change and velocity of water currents affects the compartmentalization of the network.